AB0504 Association between health-related quality of life (HRQOL) and ACR improvement among rheumatoid arthritis (RA) patients treated with secukinumab. (23rd January 2014) - Gnanasakthy, A.; Kosinski, M.; Genovese, M.; Mallya, U.; Mpofu, S.
Abstract : Background: Secukinumab has demonstrated improvement of signs and symptoms in RA patients in a phase 2 randomized controlled trial. 1 In this analysis of the same study, we assessed the association between the improvement in the signs and symptoms of RA and HRQoL. Objectives: To evaluate the HRQoL benefits associated with American College of Rheumatology (ACR) improvement among RA patients treated with secukinumab. Methods: Adult RA patients (n=237) on methotrexate were randomized equally to receive monthly s.c. injections of secukinumab 25mg, 75mg, 150mg, 300mg or placebo. Primary efficacy endpoint consisted of the proportion of patients achieving the ACR 20 response at week 16. HRQoL was measured at baseline, 2, 4, 8, 12, and 16 weeks using the SF-36v2 Health Survey and the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue). At week 16, all patients treated with secukinumab combined were categorized into 4 groups based on their ACR-N scores (<20, 20-49, 50-69, and ≥70). Analysis of variance methods were used to evaluate differences in mean changes in HRQoL scores from baseline to week 16 across the 4 groups of patients. Results: Nearly one-half (45%) of all patients treated with Secukinumab achieved ACR 20 response, while 18% and 5% of patients reached ACR 50 and ACR 70, respectively. Statistically significant and clinically meaningful improvement in HRQoL scores were observed across all SF-36v2 and FACIT-Fatigue scales among patients who achieved ACR 20. Mean SF-36v2 and FACIT-Fatigue scores improved incrementally across the ACR-N categories. Among patients who were assigned to ACR-N category 20-49, mean score improvement ranged from 2.2 to 7.5 points across SF-36v2 and FACIT-Fatigue scales. Mean score improvement ranged from 3.4 to 10.0 points across SF-36v2 and FACIT-Fatigue scales among patients assigned to the ACR-N 50-69 category. Lastly, mean score improvement ranged from 8.8 to 16.3 points across SF-36v2 and FACIT-Fatigue scales among patients assigned to the ACR-N≥70 category. Patients in the ACR-N category of <20 showed no significant improvement in HRQoL scores. Conclusions: In patients on secukinumab with greater ACR responses there were associated relevant benefits in the patients overall physical, social, role functioning, and psychological well-being. References: Genovese, M. et al. One Year Efficacy and Safety Results of a Phase II Trial of Secukinumab in Patients with Rheumatoid Arthritis. ACR congress, 4-9 November, 2011, Chicago, USA. A 401. Disclosure of Interest: A. Gnanasakthy Shareholder of: Novartis Pharmacuticals Corporation, Employee of: Novartis Pharmacuticals Corporation, M. Kosinski Consultant for: Novartis Pharmacuticals Corporation, M. Genovese Grant/Research support from: Novartis, U. Mallya Employee of: Novartis Pharmacuticals Corporation, S. Mpofu Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG